The influence and contribution of fine mode particles to aerosol optical properties during haze events at the foothills of Himalaya-Karakorum region. (1st December 2022) - Mohyuddin, Saima; Ikram, Muhammad; Alam, Khan; Bibi, Samina; Ahmad, Maqbool; Haq, Ehtiram Ul
Abstract: In the last decade, the regional haze is considered as one of the most devastating weathers which causes serious impacts on air quality, human health, and transportation over the Indo-Gangetic Plain, particularly the eastern part of Pakistan. In this paper for the first time, the long-term characterization of aerosols optical properties during haze events were carried out using ground-based Aerosol Robotic Network (AERONET) and Moderate Resolution Imaging Spectroradiometer (MODIS) onboard the Terra satellite over Lahore and Faisalabad for the period of 2009–2018. Firstly, the MODIS Aerosol Optical Depth (AOD) was correlated with AERONET AOD and reported a high degree of R-squared correlation of value 0.78 between two datasets for the months of October, November and December during the study period (2009–2018). After validation of data, the daily averaged AOD and Angstrom Exponent (AE) values exceeding 1 were selected as heavy haze events. Then the aerosol optical properties such as AOD, AE, Volume Size Distribution (VSD), and Fine Mode Fraction (FMF) of AOD were retrieved from AERONET and MODIS for further analysis. The distribution of AOD and AE showed that most of the values were greater than 1.3 and 1.1, respectively, during haze events over both study sites. The daily averaged profile of aerosol VSD exhibited a bimodal lognormal distribution having dominant fine mode peaks at radius between 0.19 and 0.25 μm as compared to coarse modes peaks. Furthermore, the contribution of fine-mode AOD to the total AOD was quite higher (i.e., 86–98%) during haze events showing the greater contribution of fine mode aerosol particles. The correlation of AE with AOD and FMF revealed that the pronounced aerosol types were fine mode aerosol particles originated due to biomass burning and urban/industrial emissions during haze events. These types of fine mode aerosol particles were also confirmed with Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) subtype measurements. Furthermore, the back trajectories revealed that most air masses were received from the local/regional aerosol sources, showing the contribution of fine mode aerosol particles to haze events whilst some of the trajectories were from Afghanistan, Iran, and India showing long range transportation of air masses to the receptor sites. Graphical abstract: Image 1 Highlights: Enhanced contribution of biomass burning & urban-industrial emissions to haze development. Characterization of aerosol optical properties indicated the existence of ∼96% of fine aerosols. Abatement policies are urgently needed to mitigate the anthropogenic emissions in order to overcome on haze formation.